Making habitat connectivity a reality. Issue 6 (13th September 2018) - Keeley, Annika T. H.; Basson, Galli; Cameron, D. Richard; Heller, Nicole E.; Huber, Patrick R.; Schloss, Carrie A.; Thorne, James H.; Merenlender, Adina M.
Abstract: Although a plethora of habitat‐connectivity plans exists, protecting and restoring connectivity through on‐the‐ground action has been slow. We identified challenges to and opportunities for connectivity conservation through a literature review of project implementation, a workshop with scientists and conservation practitioners, 3 case studies of connectivity projects, and interviews with conservation professionals. Connectivity challenges and solutions tended to be context specific, dependent on land‐ownership patterns, socioeconomic factors, and the policy framework. Successful connectivity implementation tended to be associated with development and promotion of a common vision among diverse sets of stakeholders, including nontraditional conservation actors, such as water districts and recreation departments, and with communication with partners and the public. Other factors that lead to successful implementation included undertaking empirical studies to prioritize and validate corridors and the identification of related co‐benefits of corridor projects. Engaging partners involved in land management and planning, such as nongovernmental conservation organizations, public agencies, and private landowners, is critical to effective strategy implementation. A clear regulatory framework, including unambiguous connectivity conservation mandates, would increase public resource allocation, and incentive programs are needed to promote private sector engagement. Connectivity conservation must move more rapidly from planning to implementation. We provide an evidence‐based solution composed of key elements for successful on‐the‐ground connectivity implementation. We identified the social processes necessary to advance habitat connectivity for biodiversity conservation and resilient landscapes under climate change. Abstract : Article impact statement : Key to connectivity implementation success is a common vision among stakeholders and communication among and between partners and the public.